Analisis Seberapa Edukatif Wisata di The Great Asia Africa - Rajati, Jenar; Sirait, Angelina Nathasya; Dyanta, Nabiila; P, Novita; Tohawi, Widiya Nurhidayah; Abdul Rozak, Rama Wijaya; Sukriah, Erry (Journal of Tourism and Creativity, 2023)
The Great Asia Africa is a tourist destination that presents replicas of buildings from various countries on the Asian-African continent. Also, this tour does not only present building replicas but also displays cultural aspects from the countries on this tourist destination. This research aims to find out how educative tourism is at The Great Asia Africa, using quantitative methods through distributing questionnaires to visitors we met at the tourist attractions, as well as to visitors who had visited this tourist spot before, and then we managed to reach one hundred respondents. After the data was collected, we analyzed it and found that this tour was already quite educative, but still needed further development to make it even more educative. Many of the visitors thought that this tourist destination should add boards that explaining information about knowledge at each country and the culture of each of these countries. Then it is necessary to have tour guide activities that explain knowledge from each country so that visitors get optimal experience and knowledge and making The Great Asia Africa as a best educational tour in Indonesia.